Development of innovative electronic student worksheet (E-LKPD) based on somatic auditory visual intellectual (SAVI) on salt hydrolysis topic - Ratri, Monica Cahyaning; Tina, Elisabeth Patricia Ito (Jurnal Pendidikan Kimia, 2024)
A low understanding of salt hydrolysis and a lack of mastery of mathematics in the calculation section is a problem in learning chemistry. Therefore, this research aim is to produce a good electronic student worksheet (E-LKPD) based on SAVI learning model by determining the quality of LKPD in terms of (1) feasibility and (2) student response. This research and development (R&D) used a 4D development model that was modified to 3D. The research instruments used were interview and validation sheets, test items in the E-LKPD, and student response questionnaires. The research sample consisted of 10 students of class XI MIPA. The results showed that (1) the developed E-LKPD has good quality because it met valid criteria with a percentage of 90% in terms of material and 87% in terms of media. The average score of E-LKPD effectiveness is 78 (high criteria), and practically average score of E-LKPD based on students' response questionnaire is 94.4%; (2) students said that E-LKPD can help them learn and the material is exposed clearly (92.5%), can be used for independent study (97.5%), and the design of the E-LKPD is attractive (95%). Based on the research results, SAVI-based innovative E-LKPD can be used in chemistry learning on salt hydrolysis topics.